Two-Stage Arthrodesis after an Infected Total Knee Replacement Using a Coupled Nail and Dual-Plate Construct: A Third-World Solution and Review of Options - Marlon M. Mencia; Raakesh Goalan; Atiba Akii Bua (Case Reports in Orthopedics)
Infection following total knee arthroplasty is a serious and increasingly common complication. Several treatment options are available. Although a two-stage revision remains the gold standard, salvage procedures are sometimes needed. We describe a case of an infected knee arthroplasty that was salvaged using a novel technique combining two linked intramedullary nails and bilateral compression plating.